Admission after sleep surgery is unnecessary in patients without cardiovascular disease. (15th September 2014) - Rotenberg, Brian; Theriault, Jenna; Cheng, Horace; Fuller, John
<x xml:space="preserve">Abstract</x> Objective/Hypothesis Evidence is lacking to guide whether patients with obstructive sleep apnea (OSA) require mandatory postoperative monitoring when undergoing multilevel sleep surgery. The purpose of this study was to examine the respiratory complication rate following OSA surgery and identify which patients benefit from monitoring after surgery. Study Design A prospective study was conducted. Methods Fifty patients (age 45.4 ± 12.4; male 39, female 11), with sleep study‐proven OSA (apnoea/hypopnoea index [AHI] 24.3 ± 22.2) underwent multilevel sleep surgery. All patients had the St. Joseph's OSA risk score calculated preoperatively and then again within the postanesthesia care unit (PACU). The patients were then stratified into two categories: safe for same‐day discharge and requiring admission for overnight O2 saturation monitoring. Groups were compared across age, sex, AHI, body mass index, mean O2 saturation, minimum O2 saturation, length of time in PACU, narcotic use, smoking, surgery type, and other comorbidities. The St. Joseph's OSA Risk Tool was applied. Results Seventy‐eight percent of patients met criteria for same‐day discharge, and 22% required admission. For the discharged patients, we had a 0.0% readmission or complication rate for OSA‐specific reasons. For the admitted patients, we had no OSA‐specific complications while admitted to hospital. No variables consistently predicted complications or need for admission. Conclusions The incidence of respiratory events requiring intervention following multilevel sleep surgery is very low. Most patients with OSA undergoing surgery can be safely discharged home without any subsequent respiratory complications. In addition, those patients admitted for monitoring after surgery do not benefit from their admission. Level of Evidence: 2b. Laryngoscope, 125:498–502, 2015